Investigating the impact of wave energy in the electric power system - A case study of southern Sweden - von Sydow, Tyra (My University, 2014)
The aim of this thesis has been to investigate the impact of wave energy in the electric power system of southern Sweden. How does wave energy correlate with wind power generation in the area, and can a less variable generation pattern from wave energy allow it to have a higher investment cost than wind energy? The study has been performed using meteorological data for the region from the European Centre for Medium-Rage Weather Forecasts, ECMWF, and a computer model of the electricity system. The weather data was analysed to gain a better understanding of wave power generation in general and in the area, and also to investigate the correlation between wave and wind energy. The effects of wave power on the electricity system have been analysed by using a cost-minimizing model of the electricity generation system, developed outside of this thesis. The main outcome of this thesis is that there are benefits of combining wind power generation in southern Sweden with wave power generation on the Swedish west coast, compared to only increasing wind power generation equally much. The benefits are in terms of reduced system operational costs, and the savings are in the range of 1% of the system operational cost, explained by a reduction in peak cost, lower cycling cost and less curtailment of wave and wind power generation. Since the two sources are highly correlated in the area, wave power in general is available at the same time as wind power is available, and thus the gain of combining the two sources in this specific area is reduced. In an area with lower correlation between waves and winds, the gains of combining the two sources could be higher. When it comes to the cost of the wave power compared to wind power, the outcome is that the determining factor for how the costs are related is the capacity factors. The higher capacity factor for one of the investigated technologies within this thesis was found to enable wave power to cost about 50% more than wind power per generator capacity. The system benefits of having a mix of wave and wind compared to wind only further increases this cost difference per generator capacity by one or two percentage. Wave power also has other benefits compared to wind power, such as higher public acceptance and higher energy density in the resource. The wave power industry might be in the starting blocks of a great exploitation in the coming years. Experience from the wind and solar industry tells that once things start happening, the growth in installations may be explosive. Future development on prices, investment trends, public acceptance etc., will govern the development in the wave power industry.
Keywords: Energi; Energiteknik; Energy; Energy Engineering